PENGARUH TAX AMNESTY DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PELAYANAN FISKUS SEBAGAI PEMODERASIAN - Yusak David Hizkiel; Ngadiman (Fakultas Ekonomi Universitas Tarumanagara, 2025)
This study aims to analyze the effect of tax amnesty and fine tax on non-employee taxpayer compliance against fiscus services as moderating variables. Quantitative research method is used in this study. The object of this study are all non-employee individual taxpayers registered at KPP Pratama Jakarta Matraman. The sample in this study were selected using random sampling method. Multiple regression analysis is used and analyzed using SPSS 25 test tool. The results show that tax amnesty has an effect on taxpayer compliance, fine tax have no effect on taxpayer compliance, fiscus services has no effect on taxpayer compliance. Fiscus services in this study can moderate the relationship between tax amnesty on taxpayer compliance and fiscus services cannot moderate the relationship between fine tax on taxpayer compliance.